INVENTORY OF THE MOST INVASIVE ALIEN PLANT SPECIES OF LATVIA IN THE “DAUGAVAS LOKI” NATURE PARK (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
During the realization of the scientific research program for mapping of the most invasive plant species of Latvia in the “Daugavas Loki” nature park (NP) field surveys were carried out during spring, summer and autumn seasons in 2016. In total 100 quadrats were surveyed. Invasive alien plants are species that are non-native to an ecosystem, and may cause a negative effect on environmental quality or human health. The obtained results indicate that the number of invasive alien plants species identified in 2016, i.e. 32 species, considerably increased in comparison with data about the distribution of invasive species given in the nature management plan of the “Daugavas Loki” NP in 2010, when only three species were mentioned. Many invasive plant species have been found in the ruderal biotopes – roadsides in the territory of nature park. The species with the highest number of localities are Acer negundo L., Sambucus racemosa L. and Rumex confertus Willd. The monitoring of certain most invasive species makes it possible to assess the changes in species number and occupied area.